Cerai Talak Suami Non-Muslim di Pengadilan Agama - Mrs. Hartini (Fakultas Hukum Universitas Gadjah Mada, 2009)
Religious Courts were established with mandate to serve Indonesia Moslem in case settlement based on Islamic Law. The Religious Courts are Courts of limited or special jurisdiction and party (as specified in their Statutes). They differ from the General Courts which have a general jurisdiction. The jurisdiction are limited on marriage, inheritance, will (wasiat), gift (hibah), waqf (wakaf), tithe (zakat), infaq, alms (shadaqah) and Shariah Economic (Act Number 3 of 2006 on Amendment of Act Number 7 of 1989 on Religious Court ). The courts take exclusive jurisdiction in marriage affairs concerning a Moslem husband and wife relating to marriage, revocation, reconciliation and divorce where the intervention of a religious court judge is necessary. Practically, the Courts jurisdiction extends to same range in divorce matters but the party in the case is non-Moslem. The jurisdiction is based on Islamic Personality principle; first, she or he was Moslem when marriage was conducted and second, the contract based on Islamic Law.